The development of fibre-reinforced ceramic matrix composites of oxide ceramic electrolyte - Marriner-Edwards, C (2016)
Flammable solvents contained in liquid electrolytes pose a serious safety risk when used in lithium batteries. Oxide ceramic electrolytes are a safer alternative, but suffer from inadequate mechanical properties and ionic conductivity. Thin electrolyte layers resolve the issue of conductance, but accentuate the detrimental mechanical properties of oxide ceramics. The presented work has investigated oxide ceramic electrolyte reinforcement in composite electrolytes for all-solid-state batteries. Fabricating oxide ceramic electrolytes with engineered microstructure enabled development of a reinforced composite. This approach is based on the formation of 3D- porous ceramics via stereolithography printing of polymer templates from designed cubic, gyroid, diamond and bijel architectures. The microstructural parameters of templates were analysed and modified using computational techniques. Infiltration of the prepared 3D-porous electrolyte with polymeric-fibre reinforcement created the reinforced composite electrolyte. The prepared ceramic composite showed excellent reproduction of the template microstructure, good retention of ionic conductivity and enhanced mechanical properties. The final composite was composed of NASICON-type Li1.6Al0.6Ge1.4(PO4)3 oxide ceramic electrolyte and epoxy and aramid fibre reinforcement. The gyroid architecture was computationally determined as having the optimal stress transfer efficiency between two phases. The printed gyroid polymer template gave excellent pore microstructure reproduction in ceramic that had 3D-interconnected porosity, high relative density and the most uniform thickness distribution. The ceramic matrix porosity allowed for complete infiltration of reinforcement by aramid and epoxy forming the fibre-reinforced ceramic matrix composite. The interpenetrating composite microstructure with ceramic and epoxy gave a flexural strength increase of 45.65 MPa compared to the ceramic. Unfortunately, the infiltration procedure of aramid-epoxy reinforcement did not realise the full tensile strength potential of aramid fibres.